Machining of thin sections using multi-pass wire electrical discharge machining process. (5th December 2019) - Sarma, Deba Kumar; Singh, Meinam Annebushan
The increasing application of fine metallic sections in various sophisticated areas has led to the growth of advanced machining technique to produce thin metallic sections. Wire electrical discharge machining process can prove to be an effective means to machine such sections. The current work identifies the thin wall machining of H13 tool steel using Taguchi's design. An optimal parametric setting is identified using a regression model for lower kerf width ( kf ) and higher machining rate. The decrease in kf and increase in machining rate is found to be highly dominated by the variation of the input parametric conditions. Machining of thin wall sections is performed to identify the extent of minimum sections that can be machined. A mesh-like structure is observed with wall thickness of less than 80 μm. Further, to improve the surface and edge characteristics, multi pass trimming process is incorporated.